Spiritual Care in Palliative Care - Best, Megan C.; Vivat, Bella; Gijsberts, Marie-Jose (Religions (Basel, Switzerland ), 2023)
Palliative care has always included spiritual care, but the provision and inclusion of spiritual care within and across palliative care services internationally is sub-optimal. In this summary overview, we address understandings and meanings of spirituality and related terms, both generally and in the context of healthcare, and outline the importance of spiritual well-being and spiritual care at the end of life. We summarise what spiritual care involves, its benefits for palliative care patients and their families, and consider how its provision might be helped or hindered. There is currently a limited evidence base for the efficacy of interventions including spiritual and/or religious care, and large-scale studies in particular are lacking. However, those mostly small-scale and/or qualitative studies which have been conducted to date show that addressing the spiritual needs of patients in palliative care is associated with many positive outcomes for both patients and their relatives. More research in this area is necessary to develop and enhance the evidence base, and optimal provision of spiritual care requires that providers explicitly recognise the need for such care, including through providing training and support for staff.